Serological cross-reactivity using a SARS-CoV-2 ELISA test in acute Zika virus infection, Colombia. (December 2020) - Faccini-Martínez, Álvaro A.; Rivero, Ricardo; Garay, Evelin; García, Alejandra; Mattar, Salim; Botero, Yesica; Galeano, Ketty; Miranda, Jorge; Martínez, Caty; Guzmán, Camilo; Arrieta, Germán; Contreras, Hector; et al.
Highlights: Colombia is an endemic country for Dengue, Chikungunya, and Zika virus. Co-epidemic of SARS-CoV-2 with other etiologies is a cause of concern. Serological cross-reactivity in acute Zika infection was tested using a SARS-CoV-2 ELISA test. Abstract: Objectives: We investigated seroreactivity by using a commercial SARS-CoV-2 ELISA test in samples collected from different groups of individuals, including patients diagnosed to have Dengue, Zika, and Chikungunya infection between 2015 and 2019, from an endemic area in the Caribbean Colombian region. Methods: A total of 127 sera samples obtained from six different groups of individuals were included in this study: Group A: patients with confirmed SARS-CoV-2 infection; Group B: patients with symptoms suggestive of COVID-19 or asymptomatic contacts with confirmed patients; Group C: patients with acute or recent dengue virus infection; Group D: patients with acute Zika virus infection; Group E: patients with previous Chikungunya virus infection; and Group F: individuals with exposure to spotted fever group rickettsiae. Results: Overall, group A, group B, and group D showed seroreactivity to SARS-CoV-2 in 92%, 75%, and 26% of samples, respectively; furthermore, group C, group E, and group F showed 100% seronegativity. Conclusions: We found 26% of serological cross-reactivity in patients with acute Zika virus infection by using a commercial SARS-CoV-2 ELISA test. Further studies are needed to evaluate whether serological cross-reaction is maintained with time in nonacute patients with previous exposure to the Zika virus and its effect in SARS-CoV-2 serosurveys in endemic areas for this arbovirus.